Paraneoplastic bullous pemphigoid – A sign of clear cell renal carcinoma - Jackson, Stuart R. (Urol Case Rep, 2020)
Paraneoplastic bullous pemphigoid is a rare paraneoplastic syndrome. Rash is pruritic, with erythematous eruption of large subepidermal bullae over skin and often mucosal surfaces. We present an 84y woman with a three week history of erythematous rash, and 48hrs of bullae. A left clear cell renal cell carcinoma was identified on CT imaging during the presentation. Subsequent removal of the tumour resulted in resolution of bullous pemphigoid symptoms. This first-of-kind case and successful result strengthens the association between renal cell carcinoma and paraneoplastic bullous pemphigoid, arguing for a high degree of clinical suspicion in unexplained presentations of bullous pemphigoid.